SEMIOTICS OF STOPPING BY WOODS ON SNOWY EVENING - Agung Wijianto (Universitas Airlangga, 2020)
Poetry is one of the fundamentals in literature. It expresses meaning through words and communicates deeper ideas within it. Robert Frost was one of the most prominent poets of all time. His work Stopping by Woods on a Snowy Evening was one of his greatest work, it revolves around the beauty of a forest in the winter. On the surface, it may look like a simple straightforward poem; however, it contains a deeper underlying meaning. Semiotics of Poetry written by Riffaterre will be essential in this paper to dissect the poem. There are various concepts that will be applied in the dissecting the poem like indirection, heuristic and hermeneutics reading, matrix, model, variants, and hypogram. This paper seeks to find the deeper understanding of the poem rather than just a surface understanding of it.